Digital And Interactive Educational Tools For Developing Interpersonal Activity In Preschool Children (Journal of Pedagogical Inventions and Practices, 2026)
The rapid development of digital technologies has significantly influenced modern preschool education. Interactive educational tools provide new opportunities for developing children's communication, collaboration, and social interaction skills. This study examines the role of digital and interactive learning tools in enhancing interpersonal activity among preschool children. The research analyzes how digital games, multimedia learning environments, and interactive educational platforms influence children's social behavior. Quantitative and qualitative research methods were used, including classroom observation and statistical analysis of children's participation in interactive activities. The results indicate that well-structured digital educational tools can effectively support the development of interpersonal communication and collaborative learning in early childhood education